Screening for monoclonal B-lymphocyte expansion in a hospital-based Chinese population with lymphocytosis: an observational cohort study - Yue Wang; Jing Li; Peng Liu; Jiadai Xu; Zheng Wei (BMJ Open)
Objectives Screening of monoclonal B-cell lymphocytosis (MBL) has improved the early detection of B-cell lymphoproliferative disorders (B-LPDs). This study was designed to find the most cost-effective way to screen for asymptomatic B-LPD.Design Observational study.Setting A lymphocytosis screening project was conducted at a large-scale hospital among the Chinese population.Participants For 10 consecutive working days in 2018, 22 809 adult patients who received a complete blood count (CBC) were reviewed. These patients were selected from the outpatient, inpatient and health examination departments of a National Medical Centre in China.Results A total of 254 patients (1.1%, 254/22 809) were found to have lymphocytosis (absolute lymphocyte count (ALC) >3.5×109/L). Among them, a population of circulating monoclonal B-lymphocytes were detected in 14 patients, with 4 having chronic lymphocytic leukaemia (CLL) and 10 having MBL, indicating an overall prevalence of 5.5% for B-LPD (3.9% for MBL). The prevalence of CLL among the elderly patients with lymphocytosis (≥60 years) was determined to be 4.3% (4/92). In the patients over 60 years of age, the prevalence of MBL was found to be 8.7%. CD5 (−) non-CLL-like MBL was observed to be the most common subtype (8, 80%), followed by CLL-like phenotype (1, 10.0%) and atypical CLL phenotype (1, 10.0%). The receiver operating characteristic curve analysis for the CBC results revealed that the ALC of 4.7×109/L may serve as the optimal and cost-effective cut-off for screening for early-stage asymptomatic B-LPD.Conclusion In Chinese patients with lymphocytosis, there was a relatively high proportion of patients with CLL among individuals over 60 years of age. MBL is an age-related disorder. Non-CLL-like MBL was the most common MBL subtype, almost all of whom displayed a pattern of ‘marginal zone lymphoma (MZL)-like’ MBL. Lymphocytosis screening among the elderly would be effective in the detection of B-LPD and MBL.